HUBUNGAN SOSIOEKONOMI TERHADAP KEKERASAN DALAM RUMAH TANGGA MELALUI PERNIKAHAN DINI MENGGUNAKAN STRUCTURAL EQUATION MODELLING (SEM) - Alfini Yuliyanti; Gerry Sastro (CV. Denasya Smart Publisher, 2026)
Domestic violence remains a pressing issue, especially for women, and early marriage is often seen as a risk factor that can exacerbate this problem. Early marriages are also more common among communities with low levels of income and education. However, the relationship between these three aspects is rarely explored in a comprehensive way. Using national data and statistical analysis, this study explores how socioeconomic status influences early marriage, and how early marriage contributes to the risk of domestic violence. The results show that regions with lower socioeconomic conditions tend to have higher rates of early marriage. Interestingly, in areas with higher rates of early marriage, reports of domestic violence appear lower—likely due to limited access to reporting mechanisms. The study also finds that socioeconomic status indirectly affects domestic violence through early marriage. The main contribution of this study is to provide empirical evidence based on national data on the role of early marriage as a mediating variable linking socioeconomic status with the dynamics of domestic violence reporting at the regional level. These findings highlight the importance of addressing domestic violence from a broader structural perspective.